Kemampuan Pemerintah Daerah Provinsi Lampung Dalam Membayar Pinjaman Daerah Di Era Otonomi Daerah - Indrayenti INDRAYENTI; Endang Siswati Prihastuti; Fransiska Budiman (Jurnal Akuntansi dan Keuangan, 2011)
The purpose of this study was to calculate how much capacity the maximum loan amount area where the Provincial Government of Lampung make loans in accordance with the Government Regulation Number 54 of 2005, and to assess the ability to pay obligations (principal + interest) loan areas do. The hypothesis proposed is the author of Lampung provincial government can borrow to finance its budget deficit area in general accordance with the rules established by the Central Government.Research methods used are observation, documentation, and interviews. While analysis tools used is the approach that is descriptive quantitative analysis. Based on the results of calculations based on Government Regulation No. 54 Year 2005 on Regional Loan that the Provincial Government of Lampung in 2005-2007 had loans Limit or 60% general revenue budget the previous year average of Rp.632.461.846.102, - and limits the maximum loan for a period of 5 (five) years, the bank rate by 10%, and 1% commitment fee can not be done, because the resulting value does not reach the DSCR of 2.5 or more. To achieve the debt service coverage ratio (DSCR) of or equal to 2.5 for a period of 5 (five) years, 10% interest, and a commitment fee of 1% loan that can be done only by an average of Rp.342.583.020.438 , - or by 36% of the general acceptance APBDt-1 in 2005-2007.